Systematic Literature Review (SLR) on Annuity Modeling of Plantation Replanting Cost Reserves Based on the Cobb-Douglas Model - Fasa, Rayyan Al Muddatstsir; Napitupulu, Herlina; Sukono, Sukono (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2024)
Annuity is a financial concept that involves a series of periodic payments or receipts. In oil palm plantation management, the annuity concept is adapted to model and estimate the reserves required for replanting costs over time. The Cobb-Douglas model is a model that considers the contribution of various factors in the production process. This model can be used to estimate the income of plantations. This study discusses the Systematic Literature Review on Annuity Modeling of Plantation Replanting Cost Reserves through the application of the Cobb-Douglas Model using the Reporting Method of Choice for Systematic Review and Meta-Analysis (PRISMA) method. The study systematically collected and analyzed relevant literature from Scopus, Science Direct, Dimensions, and SAGE databases. The review followed a structured methodology that included four main stages: Identification, Screening, Eligibility, and Inclusion. Analysis was conducted on the datasets obtained at the Eligibility and Inclusion stages. Statistical techniques facilitated by the "bibliometrix" package in RStudio software were used to process the findings. In addition, the results can be accessed through the "biblioshiny ()" command, allowing easy access through a web interface for in-depth exploration. Based on the inclusion and exclusion criteria carried out in this study, it can be concluded that there is no research that discusses the topic of annuity modeling of plantation replanting cost reserves using the Cobb-Douglas model specifically. This can be further research on this topic.